Socially distributed leadership in elementary schools: teacher and staff leadership practice in Denmark and the USA. Issue 2 (24th December 2021) - Modeste, Marsha E.; Nguyen, Chi; Nafziger, Rhoda Nanre; Hermansen, Jonathan
Abstract : Purpose: The purpose of this study is to examine the nature of socially distributed leadership in Denmark and the USA, specifically teacher and staff leadership practices distributed in schools. Design/methodology/approach: This study used a confirmatory factor analysis and a second-order factor analysis to examine elementary USA and 0–9 Danish school educators' responses to the Comprehensive Assessment of Leadership for Learning. Findings: Findings from this analysis of leadership practice demonstrate (1) different approaches to teacher and staff leadership in Denmark and the USA; (2) the importance of a collaborative approach to developing and maintaining professional learning communities in schools in both contexts; and (3) different patterns of leadership practice that broadly reflect the local structure and approach to school leadership while responding to external policy demands. Originality/value: Drawing on the globalization scholarship, which acknowledges the connection between global policy development and local spaces of implementation, this comparative international study allowed us to examine how policy ideas are parlayed into practice through the use of a shared assessment of leadership practice. The results of this study suggest that while the work of teacher and staff leadership is important and something that educators in Denmark and the USA are engaging in to advance the overall instructional mission of their schools, the approaches taken in each context are different and reflect a local-level negotiation between contextual cultural norms and policy expectations.